Images in architecture – from murals to illuminating projections - Bąkowska, Małgorzata (Journal of Architecture and Urbanism, 2007)
As in every other domain of art, in contemporary mural painting it is possible to indicate great projects and realizations as well as failures. However, many examples confirm the thesis of an especially significant role of depicting in architectural and urban space. After all, like in other kinds of painting, the main feature here is the talent of an artist. Artistic quality of depicting in architectural scale is so important because of its aesthetical, ethical and education role. It is hard to answer the question about the future of mural paintings and the role of the new media of transmitting color and illusion in architectural space. Nowadays, in the time of instant development of science and technology, increasing tempo of life and continuous need of changes, it may turn out that the digital and hologram pictures better fulfil the expectation of the present recipient. It is not unlikely that the practical values of these techniques – their energetic and light features – might cause the elimination of traditional wall paintings which have accompanied architecture for so many ages. On the other hand, we could observe in the present culture evident “retro” tendencies – the growth of interest in the past, the recognition of traditional forms of expression, and a desire for their continuation. Materiality, touchable texture, and some mysterious load of energy executed by artists in traditional techniques are the elements acting to the advantage of old- fashioned painted walls. Paveikslai architektūroje – nuo freskų iki šviečiančių projekcijų Santrauka. Sienų tapyba, kaip architektūros elementas, per amžius turėjo įvairių paskirčių: magišką, simbolinę, estetinę. Freskos suteikė vietai prestižo, perdavė religinio turinio žinias ir įamžino svarbiausias įvykius. Kadangi sienų tapyba visuomet egzistuoja architektūriniame kontekste ir perima architektūrinės formos specifiką, jos negalime suvokti kaip visiškai autonomiško meno. Dėl savo masto, spalvos, simbolinės prasmės ir tam tikrais atvejais aukštos meninės vertės freskos yra išraiškingi orientyrai miesto erdvėje, padedantys geriau susivokti „kognityviuose žemėlapiuose“. Šalia tradicinės sienų tapybos neseniai architektūrinėje aplinkoje ėmė atsirasti naujomis technologijomis – skaitmenine, lazerine ar hologramomis – atlikti paveikslai. Jų meninė vertė yra ypač svarbi dėl jų estetinės, etinės ir edukacinės reikšmės. Reikšminiai žodžiai: architektūrinis koloritas, sienų tapyba, skaitmeniniai ir hologramų paveikslai, kompozicija, šiuolaikinės architektūros teorija, vizualinė komunikacija, dalyvavimas. First published online: 21 May 2013